Bullying : an overview and exploration of student and parent attitudes and the perceived effectiveness of the Kia Kaha programme : a thesis presented in partial fulfilment of the requirements for the degree of Masters of Arts in Psychology at Massey University, Palmerston North, New Zealand - Lockwood, Susan Anne (Massey University, 2002)
This study provides an overview of student and parent attitudes towards bullying, and explores the perceived effectiveness of the Kia Kaha programme, 2000. It includes both qualitative and quantitative data derived from questionnaires developed from the broad objectives of the programme. The sample was taken from three schools in the Greater Wellington area. One hundred and twenty student participants and their parents were tested prior to, and following, the implementation of the school- based programme. The study provides some insight into the feelings of students who have experienced bullying both from the victim and bystander's perspective. Telling, and the safety issues implicated in telling, still present as the major obstacle in the management of bullying behaviour. Parent participants offer valuable feedback regarding their perceptions of the programme's effectiveness. Parental involvement in prevention programmes represents a previously untapped resource with the potential to enhance a whole-school anti-bullying process. Parents indicated an enthusiasm and willingness to become involved if given the opportunity.
Keywords: Bullying in schools; Prevention; School violence; New Zealand; Kia Kaha